Development of E-Book Learning Media in Introducing Science for Early Childhood - Djamali, Mochamad Fadil; Kharismawati, Indah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The issue of science knowledge comprehension among early childhood children is a complex matter that requires serious attention in many countries, including Indonesia. Several studies indicate that the understanding of science knowledge among early childhood children in Indonesia is still relatively low. One of the efforts to provide a solution to these issues is the development of electronic book (e-book) instructional media. This development research employs the ADDIE model. The ADDIE model's developmental stages include analysis, design, development, implementation, and evaluation. The target audience is Kindergarten Group B children aged 5-6 years from TK Lab.School IKIP PGRI Jember. The instruments used for this research are expert media review, expert design review, expert content review, responses from small and large focus groups. Based on the response results, the understanding of participants reached 90,6%, the appeal was rated at 90,4%, with an overall average of 90,5%. The e-book's development results, based on the participants' responses, indicate that the usage of the e-book is highly suitable and effective in enhancing the understanding of science among children aged 5-6 years.